Goeken-Johnson sixth-order Runge-Kutta method - Ismail, Muhammad M. (al-Tarbiyah wa-al-ʻilm lil-ʻulūm al-insānīyah : majallah ʻilmīyah muḥakkamah taṣduru ʻan Kullīyat al-Tarbiyah lil-ʻUlūm al-Insānīyah fī Jāmiʻat al-Mawṣil, 2011)
تم في هذا البحث اشتقاق طريقة رن ج-كوتا الجديدة من الرتبة السادسة اعتمادا على طريقة رنج- كوتا من الرتبة الخامسة للباحثين David Goeken وOlin Johnson، ما يميز هذه الطريقة أنها تتطلب خمسة تقييمات لـ f فقط، في حين أن الطريقة الاعتيادية تتطلب ستة أو سبعة تقييمات لـ f، بعد ذلك تتم مقارنة هذه الطريقة بطريقة رنج-كوتا الجديدة من الرتبة الخامسة. In this paper we drive a new sixth-order Runge-Kutta method, depending on the new fifth order Runge-Kutta method of David Goeken and Olin Johnson, the property of this method is that it needs five function evaluations only where the standard method needs six or seven function evaluations, then this method is compared with the new fifth order Runge- Kutta method.